Navigational health literacy and health service use among higher education students in Alentejo, Portugal - A cross-sectional study - Jorge Rosário; Sara Simões Dias; Sónia Dias; Ana Rita Pedro (PLoS ONE, 2025)
Introduction The navigational health literacy of higher education students is fundamental to effective health management and successful health navigation, thereby improving health outcomes and overall well-being. Assessing the general and navigational health literacy levels of these students is crucial for developing targeted interventions and facilitating informed decision-making on health-related issues. This study aimed to identify the levels of general and navigational health literacy, characterise access to and utilisation of healthcare services, and analyse the differences between the mean general and navigational health literacy indices and determinants among higher education students in the Alentejo region of southern Portugal. Methodology A descriptive and cross-sectional study was conducted between 25 May and 12 September 2023 with 1979 higher education students. An online structured questionnaire comprising the Portuguese version of the European Health Literacy Survey Questionnaire – 16 items (HLS-EU-PT-Q16) and the Navigational Health Literacy Scale (HLS19-NAV), both from the European Consortium, was used. Sociodemographic data, presence of chronic disease, perceived health status, perceived availability of money for expenses, and healthcare access and utilisation variables were included. The study data were analysed using independent samples t-test, one-way ANOVA, and post hoc Bonferroni test, followed by multiple linear regression analyses at a significance level of 0.05. Multiple linear regression analysis was performed to identify factors associated with both general and navigational health literacy. The study protocol was approved by the ethics committee of the University of Évora, and all participants provided written informed consent. Results Most students (86.8%) exhibited limited general health literacy, while 13.2% demonstrated adequate health literacy. Inadequate navigational health literacy was observed in 73.4% of students. Students with lower mean general and navigational health literacy were more likely to have utilised health services. Students with chronic conditions, recent use of urgent or emergency services, and difficulties in accessing healthcare had lower health literacy. Conversely, those enrolled in health-related courses, those with good financial resources and those who had not used health services during their course had higher health literacy. In addition, lower navigational health literacy was found among displaced students, those with chronic conditions and those who had recently consulted a doctor. Higher navigational health literacy was associated with enrolment in health-related courses and adequate general health literacy. Conclusion The findings highlight the significant influence of demographic and academic factors on general and navigational health literacy among higher education students. The prevalence of limited general and navigational health literacy underscores a significant challenge for students, institutions, and health policy makers. Effective health literacy interventions should take these factors into account. Future research should examine longitudinal changes in health literacy and evaluate the impact of targeted educational programmes.